A resonant ultrasound spectroscopy study of hydrogen-absorbing intermetallic compounds - Atteberry, Jennifer Eve, author; Leisure, Robert, advisor; Eykholt, Richard E., committee member; Patton, Carl E., committee member; Migliori, Albert, committee member; Maciel, Gary E., committee member (Colorado State University. Libraries, 2004)
Resonant ultrasound spectroscopy (RUS) has been, used to study four different hydrogen-absorbing intermetallic compounds. A fundamental study of the properties of hydrogen motion within a host metal lattice was undertaken, on two different Cl5 Laves-phase compounds. These results have been obtained by determining the ultrasonic attenuation as a function of temperature from low temperatures (~0.5 K) up to room temperature and above. The hydrogen-absorbing intermetallic compounds, TiCr1.8 and LaNi5, were studied along with La-Al-Ni alloys. The temperature-dependence of the polycrystalline elastic moduli we.re determined from 3-410 K and used to calculate various elastic parameters. Ultrasonic techniques have been used to study H(D) motion in TaV2H0.18, TaV2D0.17 and TaV2D0.50, providing strong evidence for the local quantum tunneling of hydrogen in Laves-phase materials, motion that remains extremely fast even at very low temperatures. For all three materials, a relatively large attenuation peak is observed near room temperature for measurement frequencies in the range of 1 MHz. This peak is associated with H(D) hopping between hexagons of g sites, the rate-limiting step for long-range diffusion. Much smaller attenuation peaks are observed for both H and D in each material at low temperatures and attributed to local motion within a hexagon of g sites. These peaks exhibit totally non-classical behavior, with a large isotope effect on the H(D) motion. The relaxation rate is satisfactorily described by a non-classical expression, with a temperature-dependent mobile population of H(D). The parameters describing this motion for TaVi2D0.50 are in agreement with NMR spin-lattice relaxation measurements at higher temperatures. The relaxation rate for TaV2D0.17 is somewhat faster than that for TaV2D0.50. Also, the relaxation rate for H is over an order of magnitude faster than that for D for similar concentrations. The value of 0.1 eV was found for the coupling parameter between intra-hexagon g sites and strain, a parameter for which no information was previously available. The low-temperature loss peak due to the local motion of hydrogen had not been seen prior to these measurements. Although this indicated a strong isotope effect, it was only possible to speculate as to why this peak, was not observed. The current observation, of the low-temperature peak for TaV2H0.18 provides convincing details concerning the local motion of hydrogen, including parameters for the extremely fast hydrogen motion and a consistent explanation of the strong isotope effect. Previously undetected attenuation peaks, not associated with the local or long-range motion of H(D), are observed at an intermediate-temperature range as well, and are attributed to an order-disorder transition of H(D). It seems likely that this transition is related to the temperature-dependence of the mobile population. Ultrasonic measurements also were made on the Laves-phase material ZrCr2H(D)x with x(H) = 0.09, 0.15 and 0.31 and x(D) = 0.12. Attenuation peaks associated with H(D) motion between g-site hexagons are observed in all of these materials for measurement frequencies of approximately 1.5 MHz. A large isotope effect is observed, which is interpreted in terms of quantum mechanical mechanisms of diffusion. In the temperature range of our measurements, the dominant mechanism appears to be tunneling transitions between ground states. This type of motion has been discussed theoretically. However, little evidence has been, reported indicating the existence of this mechanism for motion. The current results provide strong evidence for this novel mode of hydrogen diffusion. The shear modulus of ZrCr2H0.09, ZrCr2H0.15 and ZrCr2D0.12 also has been measured. A small shift is observed in, the modulus for each material at a temperature corresponding to the relevant peak, in the ultrasonic loss, which is consistent with the interpretation that these peaks are due to H(D) relaxation. In a more applied, study, the elastic moduli of polycrystalline TiCr1.8 have been measured over the temperature range of 3-410 K. The moduli display a normal temperature-dependence, approaching 0 K with zero slope and decreasing linearly with temperature at higher temperatures. The Debye temperature, calculated from the measured moduli, is found to be 500 K. An elastic energy contribution, to the enthalpy of formation has been calculated from the present measurements and compared to the thermodynamic results. The comparison suggests that the electronic contribution to the enthalpy of formation is comparable in magnitude to the elastic contribution, but opposite in sign. Measurements such as these are useful to theorists for electronic structure calculations and for a complete understanding of hydrogen-metal materials. Temperature-dependent measurements also have been made on polycrystalline LaAlxNi5-x with x ranging from 0 to 1, The elastic moduli have been determined and corrected for porosity so that values expected for the fully-dense material were found. The temperature-dependence in this case also resembles that of ordinary metals. Poisson's ratio is nearly temperature-independent with a value around 0.31. Our experimental values for the room-temperature shear and bulk moduli are in good agreement with theoretical values. The acoustic contribution to the low-temperature specific heat is calculated. The Debye temperatures, calculated from the 3 K moduli, are in good agreement with values reported from heat capacity measurements. The results of this work should prove useful in discerning trends or correlations that could help in the selection of new metal-hydride materials.
Keywords: molecules; molecular physics